ENHANCING LEARNING INTEREST OF EIGHTH GRADERS AT SMP N 1 ABUNG SEMULI BY THE APPLICATION OF COOPERATIVE LEARNING METHOD AND MEDIA - Rini Susilowati (Universitas Muhammadiyah Kotabumi, 2020)
Abstract : Enhancing Learning Interest of Eighth Graders at SMP N 1 Abung Semuli By The Application of Cooperative Learning Method and Media.Direktorat pembelajaran always makes effort to improve education quality in Indonesia through revitalization program of Lembaga Pendidikan Tenaga Kependidikan (LPTK). One of the programs is Penugasan Dosen di Sekolah (PDS). PDS is a program which aimed to build partnership between LPTK and lab schools as well as the other partner schools. The main goal is to improve the quality of teacher candidate and professional teacher. Relating to that goal, LPTK lecturer has a duty to teach directly at partner school and collaborate with partner teacher in the attempt to prepare and conduct an interesting, effective and technological based learning in order it can engage students’ learning interest. Therefore, cooperative learning method and media in this PDS program are applied in the attempt to increase students’ learning interest in English class.